Cultural similarity effect on the relationship quality between exporters and intermediaries and export performance of SMEs - Hamir Basah, Norliza (Universiti Malaysia Sarawak, 2020)
Quality is a crucial component for developing a relationship between SME exporters and exporter intermediaries. The key role that quality plays in enhancing the performance of SMEs in foreign markets has been highlighted. Additionally, in order to support the development of such a relationship, cultural similarity is a fundamental catalyst particularly for initial stages of the internationalization process due to the belief that companies perform better in foreign markets if they possess similar cultural backgrounds. However, there have been previous studies have reported inconsistencies in findings between cultural similarity and performance. Hence, the purpose of this study is to examine what are the mechanisms in which cultural similarity can lead to relationship quality as well as performance. This current study used the Internationalization Process (IP) Theory and the Relational Exchange Theory (RET) to examine the synergistic effect of several factors on export performance within the context of Malaysian exporting SMEs and exporter intermediaries. A quantitative method was employed in this study where the primary data derived from 203 SME manufacturing exporting firms in Malaysia. Structural Equation Modeling using Smart PLS was used for data analysis. The result indicates that all hypotheses are supported. Findings may contribute to enriching the existing literature on export performance of Malaysian SMEs which use foreign intermediaries.